Appraisal of resistant genotypes against brinjal shoot and fruit borer (BSFB), Leucinodes orbonalis, Guenee (Journal of the Bangladesh Agricultural University, 2018)
The main purpose of this study was to find out the best variety of brinjal having resistance to BSFB. A pot experiment was carried out at the germplasm centre, Agrotechnology Discipline, Khulna University, Khulna during February 2014 to August 2014. The experiment was laid out in CRD using thirteen varieties with five replications. The varieties were V1=BARI begun-1, V2=BARI begun-4, V3=BARI begun-5, V4=BARI begun-6, V5=BARI begun-7, V6=BARI begun-8, V7=BARI begun-9, V8=BARI begun-10, V9=Makra, V10=Muktokashi, V11=Lalita, V12=Hazra, V13=Chaga. Data were collected on total number of shoot, total number of infested shoot, percentage of shoot damage, percentage of shoot infestation reduction, numbers of larvae per infested shoot, total number of fruit, percentage of fruit damage, percentage of fruit infestation reduction, numbers of larvae per infested fruit. Results have shown that the minimum shoot infestation was found in BARI begun-6 (29.60%, 32.40%, 29.86% and 29.38%, respectively at four different stages of eggplant). Percent of fruit infestation was minimum in V4 (BARI begun-6) (25.16%, 27.42% and 25.40% at three stages respectively).J. Bangladesh Agril. Univ. 16(2): 227-231, August 2018